Identification of THY1 as a novel thyrotrope marker and THY1 antibody-mediated thyrotrope isolation in the rat anterior pituitary gland - Horiguchi, Kotaro; Nakakura, Takashi; Yoshida, Saishu; Tsukada, Takehiro; Kanno, Naoko; Hasegawa, Rumi; Takigami, Shu; Ohsako, Shunji; Kato, Takako; Kato, Yukio (Biochemical and biophysical research communications, 2016)
Contact-dependent (juxtacrine) signaling is important for local cell-to-cell interaction and has received attention in recent years regarding its role in pituitary function, differentiation, and development. This study investigated one of the juxtacrine-related molecules, thymocyte differentiation antigen 1 (THY1), in the anterior lobe of the rat pituitary gland. Western blot analysis revealed expression of the THY1 protein in the adult rat anterior lobe. We also found that the THY1 ligand, integrin-β2 (ITGB2), is also expressed in the pituitary gland. In situ hybridization and immunohistochemical analyses showed that both THY1 mRNA and protein were present in almost, if not all, thyroid-stimulating hormone (TSH)-immunopositive cells (thyrotropes) and that ITGB2 was co-expressed in these cells. As THY1 appeared to represent a novel marker for thyrotropes, we then attempted to isolate these cells from various anterior lobe cells by the use of a THY1 antibody and a pluriBead-cascade cell isolation system. This technology allowed the isolation of thyrotropes with 83% purity at about 17-fold enrichment. Furthermore, the isolated THY1-immunopositive cells had higher Tsh mRNA levels compared with THY1-immunonegative cells and released TSH in response to thyrotropin-releasing hormone. These findings indicated that THY1 represents a potent thyrotrope marker and that the thyrotrope isolation method using the THY1 antibody may serve as a powerful tool to analyze their function including juxtacrine regulation through THY1/ITGB2 interaction. •Thymocyte differentiation antigen 1 (THY1) functions in juxtacrine signaling.•THY1 and its ligand are expressed in the anterior lobe of the rat pituitary gland.•THY1 is a novel specific marker of thyrotropes, which produce TSH.•THY1 antibody-mediated purification yields 83% thyrotrope purity (17-fold enriched).•The THY1 antibody/pluriBead-cascade cell isolation system is rapid and convenient.